Valproic acid induces CYP3A4 and MDR1 gene expression by activation of constitutive androstane receptor and pregnane X receptor pathways - Cerveny, Lukas; Svecova, Lucie; Anzenbacherova, Eva; Vrzal, Radim; Staud, Frantisek; Dvorak, Zdenek; Ulrichova, Jitka; Anzenbacher, Pavel; Pavek, Petr (Drug metabolism and disposition: the biological fate of chemicals, 2007)
In our study, we tested the hypothesis whether valproic acid (VPA) in therapeutic concentrations has potential to affect expression of CYP3A4 and MDR1 via constitutive androstane receptor (CAR) and pregnane X receptor (PXR) pathways. Interaction of VPA with CAR and PXR nuclear receptors was studied using luciferase reporter assays, real-time reverse transcriptase polymerase chain reaction (RT-PCR), electrophoretic mobility shift assay (EMSA), and analysis of CYP3A4 catalytic activity. Using transient transfection reporter assays in HepG2 cells, VPA was recognized to activate CYP3A4 promoter via CAR and PXR pathways. By contrast, a significant effect of VPA on MDR1 promoter activation was observed only in CAR-cotransfected HepG2 cells. These data well correlated with up-regulation of CYP3A4 and MDR1 mRNAs analyzed by real-time RT-PCR in cells transfected with expression vectors encoding CAR or PXR and treated with VPA. In addition, VPA significantly up-regulated CYP3A4 mRNA in primary hepatocytes and augmented the effect of rifampicin. EMSA experiments showed VPA-mediated augmentation of CAR/retinoid X receptor alpha heterodimer binding to direct repeat 3 (DR3) and DR4 responsive elements of CYP3A4 and MDR1 genes, respectively. Finally, analysis of specific CYP3A4 catalytic activity revealed its significant increase in VPA-treated LS174T cells transfected with PXR. In conclusion, we provide novel insight into the mechanism by which VPA affects gene expression of CYP3A4 and MDR1 genes. Our results demonstrate that VPA has potential to up-regulate CYP3A4 and MDR1 through direct activation of CAR and/or PXR pathways. Furthermore, we suggest that VPA synergistically augments the effect of rifampicin in transactivation of CYP3A4 in primary human hepatocytes.
Keywords: messenger RNA; Oxidoreductases, N-Demethylating; nádorové buněčné linie; receptory cytoplazmatické a nukleární; steroidní receptory; Hepatocytes; Transcriptional Activation; systém (enzymů) cytochromů P-450; Up-Regulation; Aryl Hydrocarbon Hydroxylases; ATP Binding Cassette Transporter, Subfamily B, Member 1; transfekce; upregulace; konstitutivní androstanový receptor; Cytochrome P-450 CYP3A; enzymová indukce; reportérové geny; rifampin; antikonvulziva; Promoter Regions, Genetic; Electrophoretic Mobility Shift Assay; Receptors, Steroid; Constitutive Androstane Receptor; Testosterone; Drug Synergism; Oximes; Cell Line, Tumor; Transcription Factors; N-demethylasy; Retinoid X Receptor alpha; Cytochrome P-450 Enzyme System; Transcription, Genetic; P-glykoprotein; Valproic Acid; testosteron; genetická transkripce; Enzyme Induction; Hydroxylation; polymerázová řetězová reakce s reverzní transkripcí; Luciferases; retardační test; hepatocyty; luciferasy; transkripční faktory; Genes, Reporter; Thiazoles; synergismus léků; RNA, Messenger; Humans; Anticonvulsants; Rifampin; aktivace transkripce; thiazoly; retinoidní X receptor alfa; pregnanový X receptor; Transfection; promotorové oblasti (genetika); kyselina valproová; Reverse Transcriptase Polymerase Chain Reaction; Pregnane X Receptor; hydroxylace; aromatické hydroxylasy; cytochrom P450 CYP2B6; cytochrom P-450 CYP3A; oximy; Cytochrome P-450 CYP2B6; lidé; Receptors, Cytoplasmic and Nuclear